2001
DOI: 10.1093/jexbot/52.358.1083
|View full text |Cite
|
Sign up to set email alerts
|

Low sink demand limits photosynthesis under Pi deficiency

Abstract: The role of the demand for carbon assimilates (the 'sink') in regulating photosynthetic carbon assimilation (Pn: the 'source') in response to phosphate (P(i)) deficiency was examined in tobacco (Nicotiana tabacum L.). P(i) supply was maintained or withdrawn from plants, and in both treatments the source/sink ratio was decreased in some plants by darkening all but two source leaves (partially darkened plants). The remaining plants were kept fully illuminated. P(i)-sufficient plants showed little variation in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
2
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 30 publications
(36 reference statements)
7
91
2
8
Order By: Relevance
“…Phosphate content and photosynthesis are related in several ways, and alteration of photosynthesis as a result of P starvation has been shown for several plant species, including common bean (Rychter and Randall, 1994;Mikulska et al, 1998). It has been shown that tobacco plants grown under P deficiency have reduced photosynthate demand in sink organs, resulting in carbohydrate accumulation and decrease in net photosynthesis (Pieters et al, 2001). Our data support the proposition of Morcuende et al (2007) that repression of photosynthesis may be a secondary response linked to lower demand of photosynthate and higher sugar levels during P limitation.…”
Section: Discussionsupporting
confidence: 88%
“…Phosphate content and photosynthesis are related in several ways, and alteration of photosynthesis as a result of P starvation has been shown for several plant species, including common bean (Rychter and Randall, 1994;Mikulska et al, 1998). It has been shown that tobacco plants grown under P deficiency have reduced photosynthate demand in sink organs, resulting in carbohydrate accumulation and decrease in net photosynthesis (Pieters et al, 2001). Our data support the proposition of Morcuende et al (2007) that repression of photosynthesis may be a secondary response linked to lower demand of photosynthate and higher sugar levels during P limitation.…”
Section: Discussionsupporting
confidence: 88%
“…We found differences in foliage NSC composition among seedlings regenerated on different substrates, with seedlings on DW m having a higher starch concentration than those in S, and seedlings in S having a higher concentration than those on DW s , while the soluble sugars showed a contrary pattern. Many previous studies have reported that low P would reduce the translocation of calvin cycle intermediates out of the chloroplasts into the cytoplasm, where they are metabolized into starch and accumulated within the chloroplast, thus resulting in an increase in the starch concentration in the leaves (Pieters et al 2001;AlHamdani and Sirna 2008;Hammond and White 2008). The accumulation of starch within chloroplasts was found to be accompanied by the damage and disorientation of grana and thylakoids, as confirmed in our ultrastructural investigation (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, we found that seedlings on DW s had a higher CE value than did seedlings in S, and seedlings in S had a higher value than those on DW m . Considering the similar photosynthetic pigment concentrations among the seedlings, we confirmed the view that phosphorus deficiency apparently does not affect photosynthesis through the chlorophyll content, but mainly by affecting the carboxylation capacity (Pieters et al 2001;Lin et al 2009). Moreover, low P might diminish the transportation of calvin cycle intermediates via the P translocator (Wissuwa et al 2005), leading to starch accumulation and the destruction of chloroplast, which, in return, would decrease the photosynthetic capacity.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Pieters et al (2001) observaram que a omissĂŁo de P resultou em decrĂ©scimo na exportação de carbono das folhas (fonte), que foi quatro vezes inferior Ă  exportação de carbono das folhas de plantas com suprimento adequado de P. O acĂșmulo do produto final (carboidratos) foi um fator limitante da fotossĂ­ntese em plantas sob deficiĂȘncia de P. Existem evidĂȘncias de que as plantas usam os carboidratos como recurso energĂ©tico para o perĂ­odo reprodutivo e que a alocação de carboidratos pode variar consideravelmente entre espĂ©cies (Yee & Tissue, 2005).…”
Section: Resultsunclassified